Early feeding after cesarean section: a randomized controlled trial - Minig, Lucas; Izbizky, Gustavo; Sebastiani, Mario; Otaño, Lucas (Revista del Hospital Italiano de Buenos Aires, 2004)
Objective: To determine the equivalence of different patterns of postoperative feeding on the overall patient satisfaction or dissatisfaction with the process of care during postpartum hospital stay. Methods: A randomized, controlled study of equivalence was performed in which 97 patients were offered traditional feeding after c-section (nothing by mouth between 0 and 4 postoperative hours, then advanced to liquid diet between 5 and 24 hours after surgery, and then fed with usual diet until discharge) and 103 patients were offered early feeding (solid food within 8 hours of surgery, with a minimum of 400 kcal) between December 15, 2003, and April 12, 2004, previous acceptation of a written informed consent. Both treatments were considered equivalent if the 95% confidence interval (CI) of difference between the means, was within the limits of -10 to +10 and contained the bound zero in both analyses, the as-treated as well as in the conservative intention-to-treat. The randomization occurred at the end of the surgery. Women were eligible for trial entry if they had a term pregnancy, irrespective of whether they had scheduled or intrapartum cesarean section performed under regional anthestesia. Women were excluded if they had any condition that precluded adherence to the planned intervention, if they received tocolytic drugs (magnesium sulfate, β2 agonists, calcium channel blockers), or general anesthesia. History of bowel surgery or intraoperative intestinal complications was also an exclusion criteria. Result: The preoperative and intraoperative base-line characteristics of these patients according to the assigned treatment were similar. Mean satisfaction was 73,3 mm (CI 95% 70,2-76,4) in the visual adjectival scale (VAS) in the traditional group (S.D. 16,5), and 76,8 mm (CI 95% 74,0-79,7) in the early feeding group (S.D. 13,6), with a difference between groups of -3,51 (CI 95% -7,80 0,77). Mean pain expressed in the VAS in mm was 96,0 (IC 95% 86,1-104,8) in the traditional group and 116,3 (IC 95% 105,8-125,7) in the early feeding group, difference 4,5 (IC 95% 1,07-7,90). The incidence of nausea, vomiting, time to bowel movement and the time to passage of flatus were similar between the two groups. Conclusion: The patients to whom early feeding is offered after c-section experience similar satisfaction compared to those who are offered traditional feeding, but refer less pain after surgery. The results shown in this study demonstrate that there is no need to delay nourishment until the appearance of intestinal sounds in these patients
Keywords: early feeding; cesarean section; patient satisfaction; randomized controlled trial; ileus